Roofless Workers’ Movement and sub-proletarianization: elements for a debate on the working class in Brazil - Goulart, Débora (Pontifícia Universidade Católica de São Paulo, 2012)
This article attempts to characterize the activists of the Movement of Roofless Workers (MTST)as part part of the contemporary proletariat, highlighting the potential for resistance of theurban sub-proletariat and arguing against the hegemonic vision of this part of the workingclass as “informal workers” and/or individual enterpreneurs.